Design of Small Dual Band Microstrip Antenna for Broadband Applications - Parbhane, R. S. (Acta Technica Jaurinensis, 2014)
In this article, a small dual band rectangular slot antenna for broadband application is presented. The antenna is being excited by capacitively coupled probe feed. The antenna consists of rectangular slot from the center of the patch. The rectangular slot is being used to obtain dual frequencies of 2GHz and 3.34GHz.Instead of a rectangular feed strip, antenna is excited by a triangular feed strip with same dimension. Triangular feed strip is used to obtain a broad band frequency range. The size of the antenna is 100×100×1.6mm3with the ground of same dimension. The proposed antenna is simulated and optimized using IE3D simulation software.